The Dynamics Of The Digital Economy On The Export Performance Of Indonesian MSMEs - Hersusetiyati; Chandra, Martin Purnama (Yayasan Sinergi Kawula Muda, 2024)
This research reveals the dynamics of the digital economy and its impact on the export performance of Indonesian MSMEs. Utilizing recent data and international relations theory, this research identifies the significant transformations taking place in global trade patterns due to the shift towards a digital economy. Indonesian MSMEs play a key role in the country's exports, and the dynamics of the digital economy have provided new opportunities and challenges for their export growth. The analysis in this research includes positive effects such as greater global market access, operational efficiency, and improved competitiveness. However, challenges such as changes in consumer demand, intensified competition, and data security must also be addressed. Through an in-depth understanding of the dynamics of the digital economy, Indonesian MSMEs can optimize their export performance, create new strategies, and improve their competitiveness in the ever-changing global market.